2021
DOI: 10.1088/1742-6596/1882/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

The Investigative Science Learning Environment (ISLE) approach to learning physics

Abstract: In a plenary talk “Investigative Science Learning Environment (ISLE): helping students learn physics by practicing it and be empowered in the process” at the SEA-STEM 2020 conference I (Eugenia Etkina) described the ISLE approach to learning and teaching physics, shared examples of activities and presented evidence of student learning. In this paper I, with my collaborators David T. Brookes and Gorazd Planinsic will briefly summarize my presentation and provide a list of resources for those who wish to learn m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…During the pilot phase, we revised the goals and objectives of the lab component of the courses [1]. Our latest implementation emphasizes observational experimental skills and critical thinking inspired by the ISLE framework of [2] together with [3].…”
Section: Implementation and Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the pilot phase, we revised the goals and objectives of the lab component of the courses [1]. Our latest implementation emphasizes observational experimental skills and critical thinking inspired by the ISLE framework of [2] together with [3].…”
Section: Implementation and Demographicsmentioning
confidence: 99%
“…Our lab objectives focus on data sense-making and observational experimental skills influenced by the work of Bonn, Holmes and Wieman [3] together with the work of Etkina and Van Heuvelen [2].…”
Section: Lab Goals and The Course Designmentioning
confidence: 99%
See 1 more Smart Citation
“…One may also have to rethink the tradition of having students work through sets of discrete physics problems with only a single right answer, and instead focus on the iterative development and refinement of causal models (14). If one is aiming to incorporate communication, writing, or peer review, one may have to give students tasks that are open-ended or unstructured in order to give them "something to write about" (15,16). This is even the case in more experimental contexts, such as physics labs, which are meant to give students a taste of what it means to "do science" rather than just "learn about science" (17,18).…”
Section: The Need For More Authentic Scientific Practice In Educationmentioning
confidence: 99%
“…Investigative science learning environment (ISLE). One instructor, who was teaching an intro class with combined lecture and lab components, found that remote ISLE-like activities [14,15,16] were more effective than recorded video lectures. They noted: "My lectures which had been productive during the term were largely ineffective in the new setting...…”
Section: Skillsmentioning
confidence: 99%